(untitled) (The Research of Medical Science Review, 2025)
Desertification and habitat destruction, which climate change aggravates, pose grave threats to Pakistan’s special animals and natural areas. This review shows alarming impacts of these environmental problems on species like the Indus River Dolphin, Markhor, Snow Leopard, and Himalayan Brown Bear. The sensitive ecosystems of Pakistan are subjected to too much grazing, cutting down trees, growth of cities, and poor farming practices, with which growing pressures push many species towards extinction.It analyzes how habitat loss and land degradation impact plants and animals. For instance, tree-cutting and wetland desiccation have significantly reduced the Indus River Dolphin habitats, while fewer prey species in mountainous regions made Snow Leopards more vulnerable. The analysis also underlines the social and economic challenges created by fewer wild animals that have upset the balance of nature and affected people dependent on natural resources for their livelihood. To counter this, the study offers conservation measures such as reforestation, sustainable agricultural practices, and modern monitoring tools like Geographic Information Systems. Also, more community involvement and enforcement of wildlife protection laws are necessary to reverse biodiversity loss. This is meant to bring out integrated approaches to conserve wildlife and natural resources in a sustainable manner. There is a critical need for immediate action to be taken to protect the biodiversity of Pakistan, preserve ecological stability, and human well-being dependent on such ecosystems. Findings may form a basis for policies and conservation strategies that find a balance between environmental preservation and development.